2016
DOI: 10.1371/journal.pone.0151507
|View full text |Cite
|
Sign up to set email alerts
|

Coupling Demographic and Genetic Variability from Archived Collections of European Anchovy (Engraulis encrasicolus)

Abstract: It is well known that temporal fluctuations in small populations deeply influence evolutionary potential. Less well known is whether fluctuations can influence the evolutionary potentials of species with large census sizes. Here, we estimated genetic population parameters from as survey of polymorphic microsatellite DNA loci in archived otoliths from Adriatic European anchovy (Engraulis encrasicolus), a fish with large census sizes that supports numerous local fisheries. Stocks have fluctuated greatly over the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 65 publications
1
14
0
Order By: Relevance
“…These data agree with those reported by Giannoulaki et al (2013), who found in the Mediterranean Sea a preference for spawning areas at depths of 40 -150 m, and with those of Saraux et al (2014), who identified two recurrent areas further from the coast (isobaths of ∼70 to 100 m) and unfavourable areas close to the coast in the Gulf of Lion for adult anchovy. The results of the present study show significantly different distributions of eggs and larvae over the years, in line with the notion that the biomass of small pelagic species undergoes wide fluctuations over time throughout the world (Brander, 2007;Leonori et al, 2009Leonori et al, , 2011Ruggeri et al, 2016a). The PCA data explained the environmental variability mainly in terms of depth and chlorophyll-a, but also stressed the importance of zooplankton abundance.…”
Section: Discussionsupporting
confidence: 88%
“…These data agree with those reported by Giannoulaki et al (2013), who found in the Mediterranean Sea a preference for spawning areas at depths of 40 -150 m, and with those of Saraux et al (2014), who identified two recurrent areas further from the coast (isobaths of ∼70 to 100 m) and unfavourable areas close to the coast in the Gulf of Lion for adult anchovy. The results of the present study show significantly different distributions of eggs and larvae over the years, in line with the notion that the biomass of small pelagic species undergoes wide fluctuations over time throughout the world (Brander, 2007;Leonori et al, 2009Leonori et al, , 2011Ruggeri et al, 2016a). The PCA data explained the environmental variability mainly in terms of depth and chlorophyll-a, but also stressed the importance of zooplankton abundance.…”
Section: Discussionsupporting
confidence: 88%
“…As a result of this study; a significantly higher DNA yield was observed for historical otoliths treated with Protocol 2 modified by Ruggeri et al (2016) in comparison to Protocol 1 (NucleoSpin TissueXS, Magery-Nagel). Although DNA yield was generally low, the PCR amplification success rate of contemporary otolith samples were high for the full range of fragments sizes in both the Protocol 1 and 2 (Figure 2 and Figure 3).…”
Section: Resultsmentioning
confidence: 68%
“…During population bottlenecks, the reduction in effective population size ( N e ) can produce transient genetic sweeps that lead to locally adaptive genotypes [ 81 ]. A recent study showed that the effective sizes of anchovy populations in the Adriatic are several orders of magnitude smaller than census sizes [ 82 ]. These small effective sizes appear to be in part a legacy of a severe reduction in population abundances from overharvesting in the 1980s.…”
Section: Discussionmentioning
confidence: 99%